2021
DOI: 10.31235/osf.io/ntrpx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 and the scientific publishing system: Growth, open access and scientific fields

Abstract: We model the growth of scientific literature related to COVID-19 and forecast the expected growth from 1 June 2021. Considering the significant scientific and financial efforts made by the research community to find solutions to end the COVID-19 pandemic, an unprecedented volume of scientific outputs is being produced. This questions the capacity of scientists, politicians and citizens to maintain infrastructure, digest content and take scientifically informed decisions. A crucial aspect is to make predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The same pattern is also supported by previous studies in different databases such as WoS, Scopus, and Dimensions [5,15,37,38]. Analysis of the evolution of the publications and OA types over time showed that, although an increasing tendency is observed in all OA types, Green OA articles decreased in favor of Gold OA journals during the pandemic, in line with the findings of Nane et al [11].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The same pattern is also supported by previous studies in different databases such as WoS, Scopus, and Dimensions [5,15,37,38]. Analysis of the evolution of the publications and OA types over time showed that, although an increasing tendency is observed in all OA types, Green OA articles decreased in favor of Gold OA journals during the pandemic, in line with the findings of Nane et al [11].…”
Section: Discussionsupporting
confidence: 88%
“…New pressures and new opportunities were introduced for the scholarly publishing system [ 11 ]. Horbach [ 12 ] analyzed 669 articles and found that medical journals had accelerated their publication process (eg, the time between submission and publication decreased on average by 49%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the distribution of publications by type of access, there is evidence of a growing preference for open access journals in Ecuador, which is in line with the post-pandemic global trends observed by [24]. However, Ecuador still faces challenges in terms of comprehensive adoption of these practices, compared to more advanced countries in this aspect, as described in the research by [25].…”
Section: Resultsmentioning
confidence: 69%